CsrA Enhances Cyclic-di-GMP Biosynthesis and Yersinia pestis Biofilm Blockage of the Flea Foregut by Alleviating Hfq-Dependent Repression of the hmsT mRNA - Amelia R. Silva-Rohwer; Kiara Held; Janelle Sagawa; Nicolas L. Fernandez; Christopher M. Waters; Viveka Vadyvaloo (mBio, 2021)
ABSTRACT Plague-causing Yersinia pestis is transmitted through regurgitation when it forms a biofilm-mediated blockage in the foregut of its flea vector. This biofilm is composed of an extracellular polysaccharide substance (EPS) produced when cyclic-di-GMP (c-di-GMP) levels are elevated. The Y. pestis diguanylate cyclase enzymes HmsD and HmsT synthesize c-di-GMP. HmsD is required for biofilm blockage formation but contributes minimally to in vitro biofilms. HmsT, however, is necessary for in vitro biofilms and contributes to intermediate rates of biofilm blockage. C-di-GMP synthesis is regulated at the transcriptional and posttranscriptional levels. In this, the global RNA chaperone, Hfq, posttranscriptionally represses hmsT mRNA translation. How c-di-GMP levels and biofilm blockage formation is modulated by nutritional stimuli encountered in the flea gut is unknown. Here, the RNA-binding regulator protein CsrA, which controls c-di-GMP-mediated biofilm formation and central carbon metabolism responses in many Gammaproteobacteria, was assessed for its role in Y. pestis biofilm formation. We determined that CsrA was required for markedly greater c-di-GMP and EPS levels when Y. pestis was cultivated on alternative sugars implicated in flea biofilm blockage metabolism. Our assays, composed of mobility shifts, quantification of mRNA translation, stability, and abundance, and epistasis analyses of a csrA hfq double mutant strain substantiated that CsrA represses hfq mRNA translation, thereby alleviating Hfq-dependent repression of hmsT mRNA translation. Additionally, a csrA mutant exhibited intermediately reduced biofilm blockage rates, resembling an hmsT mutant. Hence, we reveal CsrA-mediated control of c-di-GMP synthesis in Y. pestis as a tiered, posttranscriptional regulatory process that enhances biofilm blockage-mediated transmission from fleas. IMPORTANCE Yersinia pestis, the bacterial agent of bubonic plague, produces a c-di-GMP-dependent biofilm-mediated blockage of the flea vector foregut to facilitate its transmission by flea bite. However, the intricate molecular regulatory processes that underlie c-di-GMP-dependent biofilm formation and thus, biofilm-mediated blockage in response to the nutritional environment of the flea are largely undefined. This study provides a novel mechanistic understanding of how CsrA transduces alternative sugar metabolism cues to induce c-di-GMP-dependent biofilm formation required for efficient Y. pestis regurgitative transmission through biofilm-mediated flea foregut blockage. The Y. pestis-flea interaction represents a unique, biologically relevant, in vivo perspective on the role of CsrA in biofilm regulation.